Luminescent temperature sensor based on [Ru(bpy)₃]²⁺ incorporated into chitosan - Tsvirko, M.; Tkaczyk, S.; Kozak, M.; Kalota, B. (Functional Materials, 2013)
A novel luminescent temperature sensor using ruthenium(II)-tris(2,2´-bipyridil) ([Ru(bpy)₃]²⁺) incorporated into chitosan polymer matrix was developed. The sensor exhibits completely reversible and stable luminescent response (λ exc = 455 nm, λ em = 605 nm), strong temperature sensitivity (–2.0 %/°C), significant luminescence intensity decrease (~10×) in the range of 25–75°C, and stable construction. Ruthenium(II) complex oxygen sensitivity was avoided by use of matrix (chitosan) with low oxygen permeability coefficient. In the absence of oxygen the sensor shows a little higher accuracy and stability of luminescence response than under oxygen conditions. Moreover, this sensor, due to biocompatibility of the used ingredients and the emission in the red VIS-region, which is transparent for tissues, is promising for use in biological applications.